Effect of topical ophthalmic dorzolamide(2%)–timolol(0.5%) solution and ointment on intraocular pressure in normal horses. (18th December 2014) - Tofflemire, Kyle L.; Whitley, Elizabeth M.; Flinn, Allison M.; Dufour, Valerie L.; Ben‐Shlomo, Gil; Allbaugh, Rachel A.; Griggs, Angela N.; Peterson, Chimene S.; Whitley, David R.
Abstract Objective To compare the effect of commercially available solution and compounded ointment formulations of dorzolamide(2%)–timolol(0.5%) on intraocular pressure (IOP) of normal horses. Animals Eighteen clinically normal horses. Procedures A randomized, masked prospective design was used with horses divided into two equal groups. One eye of each horse was selected for topical ophthalmic treatment with either 0.2 mL of dorzolamide(2%)–timolol(0.5%) solution or 0.2 g of dorzolamide(2%)–timolol(0.5%) ointment every 12 h for 5 days. The contralateral eye of horses in both groups was untreated. Rebound tonometry was performed every 6 h starting 2 days prior to and ending 2 days after the treatment period. Results The mean IOP reduction in eyes treated with the solution or ointment formulations was 13%. Untreated eyes in both groups experienced a lesser but still statistically significant reduction in IOP. The IOP values did not return to baseline within 48 h of the last treatment. Conclusions and Clinical Relevance The commercially available solution and compounded ointment formulations of ophthalmic dorzolamide(2%)–timolol(0.5%) had similar effects on IOP in normal horses. Persistent IOP reduction following cessation of treatment may indicate prolonged drug effect or acclimation of horses to tonometry.